Door to door : a picture book - Roffey, Maureen; Lodge, Bernard (New York : Lothrop, Lee & Shepard Books, 1980)
Rhyming text and split-page illustrations provide a glimpse at the activities inside and outside a row of 12 houses.
Keywords: Toy and movable books -- Specimens; Dwellings -- Fiction; Toy and movable books; Stories in rhyme